2014
DOI: 10.1021/am505928j
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of Porous Diamond-like Carbon Electrodes for Sensing Hormones, Neurotransmitters, and Endocrine Disruptors

Abstract: Porous diamond-like carbon (DLC) electrodes have been prepared, and their electrochemical performance was explored. For electrode preparation, a thin DLC film was deposited onto a densely packed forest of highly porous, vertically aligned multiwalled carbon nanotubes (VACNT). DLC deposition caused the tips of the carbon nanotubes to clump together to form a microstructured surface with an enlarged surface area. DLC:VACNT electrodes show fast charge transfer, which is promising for several electrochemical appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 53 publications
0
24
0
1
Order By: Relevance
“…We then showed that coating the VAMWCNT with DLC resulted in porous, electrically conducting DLC films (DLC:VAMWCNT) with promising electrochemical behaviour. The DLC:VAMWCNT composite electrode exhibited fast electron transfer kinetics toward inorganic and organic redox probes, as well as high analytical sensitivity in the cyclic voltammetric determination of biomolecules (dopamine, epinephrine and paracetamol) .…”
Section: Introductionmentioning
confidence: 99%
“…We then showed that coating the VAMWCNT with DLC resulted in porous, electrically conducting DLC films (DLC:VAMWCNT) with promising electrochemical behaviour. The DLC:VAMWCNT composite electrode exhibited fast electron transfer kinetics toward inorganic and organic redox probes, as well as high analytical sensitivity in the cyclic voltammetric determination of biomolecules (dopamine, epinephrine and paracetamol) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, DLC films have emerged as an area of significant interest for certain electrochemical applications. This interest is a result of characteristic and desirable properties being realised; such as mechanical hardness, low surface roughness, enhanced elastic modulus and chemical inertness, as well as its semiconductor nature, with a tuneable band gap of 1 to 4 eV (approximately) [115].…”
Section: Diamond-like Carbonmentioning
confidence: 99%
“…VACNT films have been grown on titanium grade 2 substrate (pure titanium) or titanium grade 5 (Ti6Al4V alloy) by microwave plasma assisted chemical vapor deposition (MWCVD). [56][57][58] Figure 3 shows a schematic drawing of the MWCVD reactor. The home-built MWCVD reactor chamber, shown in Fig.…”
Section: Our Developmentsmentioning
confidence: 99%